PENGARUH KETERAMPILAN PIMPINAN, KOMITMEN ORGANISASI, DAN MORAL KERJA TERHADAP KEDISIPLINAN PEGAWAI DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SURAKARTA - Ekowati, Cicilia -; Widajanti, Erni - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2013)
This study is a survey of employees in the State Property Office and Auction Surakarta. The population in this study were 34 employees. The sampling technique using census. Types of data using qualitative data and quantitative data. Source of data using primary data and secondary data. The technique of collecting data using questionnaires, interviews, and literature. The results showed that there was a significant influence on the leadership skills of employee discipline in the State Property Office and Auction Surakarta. There was a significant effect of organizational commitment to employee discipline in the State Property Office and Auction Surakarta Surakarta, no significant effect on the morale of discipline employees in the State Property Office and Auction Surakarta Surakarta. Organizational Commitment dominant influence on employee discipline in the State Property Office and Auction Surakarta not truth but morale variable is the variable that the dominant influence on employee discipline . Keywords: leadership skills, organizational commitment, morale, employee discipline